Punjab police rules : as applicable to Punjab, Haryana, H.P. and Delhi - Koshy, K. (Rohtak, 1992)
The Punjab Police Rules are truly monumental. They have with stood the test of time now for nearly a century and are still being followed as religiously as they were a century ago, not only in this country but also in Pakistan.
Keywords: Police-Punjab-law and legislation